Environmental and Socio-Economic Effects of Underground Brown Coal Mining in Piła Młyn (Poland) - Rurek, Mirosław; Gonia, Alicja; Hojan, Marcin (Land (Basel), 2022)
In Poland, apart from opencast mining, brown coal (lignite) was also mined by underground methods. This is related to glaciotectonic disturbances leading to deposition of Miocene coal in the form of folds (synclines and anticlines). The highest number of underground brown coal mines in the 19th century was recorded in western Poland. In northern Poland in the second half of the 19th century there were active underground brown coal mines in Piła Młyn. The study aims to present the environmental and socio-economic effects of discontinuing lignite mining. It is a unique example of cultural heritage and influences the tourist development of the region. To this end, historical topographic maps were used together with data from LIDAR (Light Detection and Ranging) laser scanning, available descriptions and scientific articles about coal mines. Information from the local inhabitants and representatives of the “BUKO” Association (the Association of Inhabitants and Enthusiasts of Piła nad Brdą “BUKO”) was also obtained. As shown by the results of the analyses, changes in the environment are manifested in terrain relief and highlight the location of former coal mines. Clear land subsidence is arranged in linear sequences and occurs as single landforms. Recesses at the former extraction sites are very distinct. The socio-economic effects observed include activity of the inhabitants and development of rural areas. The area also offers good prospects for tourism as a themed mining village attracts tourists and is a unique amenity in Poland. The subject matter of this article is also of importance from the standpoint of civil engineering since post-mining areas cannot be repurposed for residential development. Due to changes in the relief in this area in places other than those analyzed, scientific research will be conducted here, which will allow to answer other hypotheses (brown coal transport).